Ten new records of marine invertebrates from the Azores - Wirtz, Peter (2020)
The sea anemones Telmatactis cricoides (Duchassaign, 1850) and Actinia n. sp., the molluscs Tonna galea Linnaeus, 1758, Vitreolina philippi (de Rayneval & Ponzi, 1854), Melanella n. sp., Phidiana lynceus (de Rayneval & Ponzi, 1854) and Anomia patelliformis (Linnaeus, 1761), the nemertine Baseodiscus delineatus (DelleChiaje, 1825) and the echinoderms Leptosynapta inhaerens (O. F. Müller, 1776) and Stichopus regalis (Cuvier, 1817), are here recorded from the Azores for the first time. The presence of the two starfish species Chaetaster longipes (Retzius, 1805) and Luidia ciliaris (Philippi, 1837) in the Azores is confirmed and the spawning behaviour of the sea urchin Echinocyamus pusillus (O. F. Müller, 1776) is described.